A Descriptive Analysis of Swear Words Used in 30 minutes or less Movie - Utami, Kadek Ayu Tata Cahya (Journal of Linguistic and Literature Studies, 2024)
AbstractThis study aims to analyze the use of swear words by Nick, the main character in 30 Minutes or Less Movie. The research questions addressed include the types of swear words used by Nick and the dominant types used. This research employed descriptive qualitative and quantitative approaches to provide a comprehensive picture of the use of swear words in the movie. The content analysis method was used to identify and categorize the types of swear words used by Nick. Qualitative data was analyzed using Miles and Huberman's theory, which included stages of data reduction, data display, and conclusion drawing. Additionally, a quantitative approach was employed to calculate the frequency of swear words to determine the dominant types. The results of the study show that Nick uses a total of 64 swear words in the movie. The type of vulgarity dominates with a frequency of 59 occurrences (92.19%), followed by obscenity with three occurrences (4.69%), then both epithet and profanity with one occurrence each (1.56%). These swear words frequently occur in contexts of high tension or stress to express frustration. In conclusion, Nick’s swear word plays a significant role in character building and enriching the narrative in 30 Minutes or Less Movie. The implication is that the use of such language not only adds depth to Nick's character but also enhances the overall authenticity and relatability of the film's portrayal of stressful situations.